PEMANFAATAN LIMBAH KULIT BUAH PINANG (Areca Catechu) DAN SEKAM PADI (Oryza Sativa) MENJADI PAPAN PARTIKEL - Hefzi, Galang (Fakultas Teknik Universitas Panca Bhakti, 2024)
Kubu Raya has extensive land with rice husk waste output amounting to 55,707 tons in 2023, and areca waste produced at 675 kg/ha. The purpose of this study is to utilize areca fruit husk waste and rice husk waste into particle boards, focusing on various aspects such as the particle board manufacturing process and the physical and mechanical characteristics of the resulting material. The research was conducted in the Laboratory of Nahdlatul Ulama University of West Kalimantan and the Materials and Construction Laboratory at the Faculty of Engineering, Tanjungpura University. The materials used include rice husk waste, areca waste, PVAC (Polyvinyl acetate) adhesive, and water. This study employs a quantitative descriptive method, with the particle board manufacturing process done manually through compression on a mold with dimensions of 30 cm x 30 cm x 1 cm. The particle board has different compositions for testing: sample A with 60% areca husk and 40% rice husk, sample B with 50% areca husk and 50% rice husk, and sample C with 40% areca husk and 60% rice husk. The resulting particle boards undergo testing following the Indonesian National Standard (SNI) for particle boards. The effective results from the sample variations (A, B, and C) were found in sample C, with a density value of 0.53 g/cm³, moisture content of 10.98%, thickness swelling of 10%, and MOR value of 0.0000180 kgf/cm².